Limb Position Influences Peripheral Arterial Stiffness Reduction with Reactive Hyperemia - Ronald E. Jackson; Natalia S. Lima; Sara R. Sherman; Brooks A. Hibner; Philip S. Clifford (Artery Research)
Abstract The mechanism behind the acute reduction in peripheral arterial stiffness with reactive hyperemia is presumed to be flow-mediated; however, this has not been clearly demonstrated. We hypothesized that a larger reactive hyperemia magnitude would result in a greater reduction in peripheral arterial stiffness. Fourteen healthy young adults (5 females, 25 ± 5 yrs, mean ± SD) underwent reactive hyperemia with a rapid-release cuff on the upper arm inflated to 220 mmHg for 5 min: once with the arm positioned ~ 50ο above heart level and once with the arm positioned ~ 50ο below heart level. Brachial-radial pulse wave velocity (PWV) was measured with tonometers over brachial and radial arteries before cuff inflation and at 5, 15, and 30 min after release. Brachial blood flow was monitored with doppler ultrasound. At 5 min after reactive hyperemia, both the absolute (2.31 ± 1.22 vs 1.19 ± 1.19 m/sec, p = 0.007) and relative (24% vs 15%; p = 0.043) changes in brachial to radial PWV were greater with the arm below the heart compared to above the heart. The peak brachial blood flow was higher when the arm was below the heart compared to above the heart (477 $$±$$ ± 145 vs 369 $$±$$ ± 137 ml/min; p < 0.001). Reactive hyperemia acutely reduced peripheral arterial stiffness above and below heart level, with a greater decrease observed when the arm was positioned below the heart. These results demonstrate the contribution of conduit artery blood flow to the reduction of peripheral arterial stiffness after reactive hyperemia.